2018
DOI: 10.1152/japplphysiol.00641.2017
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal swallowing and arousal threshold in individuals with chronic spinal cord injury

Abstract: Respiratory complications are potential causes of death in patients with spinal cord injury (SCI). Nocturnal swallowing could be related to transient arousals and could lead to fragmented sleep in SCI patients. However, the impact of nocturnal swallowing on breathing and sleep physiology in SCI is unknown. The objectives of this study were 1) to determine whether nocturnal swallowing is more common in SCI than in able-bodied (AB) subjects, 2) to determine the role of nocturnal swallowing on arousal threshold (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Arousal Threshold: Arousal threshold is one of the physiologic traits that contributes to the pathogenesis of SDB. 24 A recent study found that arousal threshold is significantly reduced in individuals with SCI, indicating increased arousal propensity, 34 which may contribute also to the mechanism of sleep disturbances in SCI.…”
Section: Sci/d-specific Pathophysiologic Factorsmentioning
confidence: 99%
“…Arousal Threshold: Arousal threshold is one of the physiologic traits that contributes to the pathogenesis of SDB. 24 A recent study found that arousal threshold is significantly reduced in individuals with SCI, indicating increased arousal propensity, 34 which may contribute also to the mechanism of sleep disturbances in SCI.…”
Section: Sci/d-specific Pathophysiologic Factorsmentioning
confidence: 99%
“…Three participants with cervical SCI and four with thoracic SCI required the use of Zolpidem. Zolpidem has been used for this purpose in previous studies with SCI participants (Rizwan et al, 2018; Sankari, Bascom, & Badr, 2014; Sankari, Bascom, Chowdhuri, et al, 2014). It has been shown to have minimal or no effect on upper airway collapsibility, ventilation, PaCO 2 , SaO 2 , the ventilatory response to CO 2 , or the respiratory disturbance index (Beaumont et al, 1996; Manning et al, 1992; McCann et al, 1993; Peng & Prabhakar, 2004; Quera‐Salva et al, 1994; Xie et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple mechanisms predispose to the development of SDB in SCI 29. These include increase upper airway collapsibility,30 a reduced dilator muscle responsiveness/effectiveness,31 a reduced arousal threshold,32 and an unstable ventilatory control system 21. The increased upper airway collapsibility can be due to multiple physiological and/or anatomical factors.…”
Section: Sleep-disordered Breathing In Scimentioning
confidence: 99%